Жанрові особливості «Лексикону інтимних міст» Юрія Андруховича та «Абетки» Чеслава Мілоша - Випасняк, Галина Олегівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
1. Статтю присвячено розгляду жанрових особливостей «Лексикону інтимних міст» Юрія Андруховича та «Абетки» Чеслава Мілоша. Твори такого характеру важко піддаються певним жанровим дефініціям, оскільки поєднують риси багатьох жанрів. У романах-лексиконах Ю. Андруховича і Ч. Мілоша виділено елементи автобіографії, есею, мемуару, травелогу (розповіді про мандри) та власне роману. The article is dedicated to the investigation of genre special features in “The Lexicon Of Intimate Cities» by Yuriy Andrukhovych and “The Alphabet» by Czeslaw Milosz. The genre of this type of writings is very hard to define because of mixing different genre patterns. Cognitive approach to genre is the most suitable method for analyzing postmodernist mixed genres texts. Cognitive aspects give an ability to distinguish the most visible components of different genre patterns and determine the dominant one, which can be taken as a basis for genre definition of various types of texts. Elements of autobiography, memoirs, essay, travelogue and novel actually are visible in analyzed novels of Y. Andrukhovych and C. Milosz. Mixing of these elements are exactly the distinctive features of novel-lexicon as a special genre type of novel in postmodern literature.
Keywords: жанр; роман-лексикон; автобіографія; мемуари; есей; травелог; Ю. Андрухович; Ч. Мілош